International Ovarian Tumor Analysis (IOTA) Scoring System to Predict Ovarian Malignancy Preoperatively - Yuri Feharsal; Andi D Putra (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To compare diagnostic performance of International Ovarian Tumor Analysis (IOTA) scoring method with Risk of Malignancy Index-4 (RMI-4) and Sassone Morphology Index to predict ovarian malignancy preoperatively. Method: Retrospective study with 119 subject who underwent surgical removal of ovarian tumor and performed histopathological examination at Dr. Cipto Mangunkusumo Hospital on January to December 2013. Demographic status, ultrasound scans, CA-125 level and histopathological result were collected to calculate the score of each method. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated by comparing each score with histopathology result. Comparison of diagnostic performance was analyzed by ROC curve. Result: There were 51.26% subjects with benign tumor and 48.74% subjects with malignant tumor. Result was analyzed with sensitivity test (IOTA simple-rules, IOTA subgroup, RMI-4 and Sassone): 98%, 88%, 86% and 79%; specificity: 74%, 67%, 61% and 89%; positive predictive value: 78%, 72%, 68% and 87%; negative predictive value: 98%, 85%, 82% and 81%; and accuracy: 86%, 77%, 73% and 84%. AUC value for IOTA simple-rules, IOTA subgroup, RMI-4 and Sassone were: 0.86, 0.78, 0.73 and 0.84. Comparison of these results were significant with p = 0.000. Conclusion: IOTA simple-rules had better sensitivity, negative predictive value and accuracy than IOTA subgroup, RMI-4 and Sassone morphology index to predict ovarian malignancy preoperatively. [Indones J Obstet Gynecol 2016; 1: 42-46] Keywords: iota, ovarian neoplasm, risk of malignancy, scoring